Prospective interactive influence of financial strain and emotional nonacceptance on problematic alcohol use during the COVID-19 pandemic. (2nd January 2021) - Gratz, Kim L.; Scamaldo, Kayla M.; Vidaña, Ariana G.; Richmond, Julia R.; Tull, Matthew T.
ABSTRACT: Background : Researchers have highlighted the risk for alcohol use problems in the context of COVID-19, although the factors associated with this risk remain unclear. Objectives : This study examined the prospective relation of baseline financial strain (reported at the beginning of the pandemic) to problematic alcohol use one month later, as well as the moderating role of emotional nonacceptance. We hypothesized that financial strain would be more strongly associated with problematic alcohol use one month later among participants with high (vs. mean or low) levels of nonacceptance. Methods : Shortly after COVID-19 was declared a pandemic by the WHO and national emergency by the U.S. President (on March 11 and 13, 2020, respectively), a U.S. nationwide community sample completed a prospective online study, including an initial assessment from March 27-April 5, 2020 and a one-month follow-up from April 27-May 21. Measures included the Family Economic Strain Scale, Difficulties in Emotion Regulation Scale, and Alcohol Use Disorders Identification Test. Participants included 254 adults reporting some alcohol use (50.4% women; mean age = 41.8). Results : Baseline financial strain was significantly positively associated with problematic alcohol use one month later only among participants with high ( b =.06, SE =.03, p =.037) versus mean ( b =.01, SE =.02, p =.677) or low ( b = −.04, SE =.02, p =.110) emotional nonacceptance. Conclusion : Individuals experiencing financial strain in the context of COVID-19 may be at risk for problematic alcohol use if they are not accepting of their emotional distress.